North Sumatra Busedah to strengthen students’ character and implementation through the fun school - Moningka, Yudha; Aprilia, Nani; Isnaeni, Bekti (Universitas Ahmad Dahlan, 2024)
Strengthening character education still needs to be done because it has been found that student's behavior is not according to applicable norms and rules. History education is one of the subjects that can potentially strengthen character education. The formulation of this research is “How is the design of North Sumatra Busedah to strengthen the character education of students and its implementation through the fun school movement?” The purpose of this research is to analyze the design of North Sumatra Busedah to strengthen the character education of students and its implementation through the fun school movement. This type of research is descriptive research. The data collection techniques used are observation and documentation. The data collection instruments used were observation sheets and history books. The research procedure was carried out by analyzing the material content in the history book used by the teacher. Then, researchers designed a new history book, North Sumatra Busedah, as a renewal of history books that contained material about the history of North Sumatra. Furthermore, researchers examined the challenges that would be faced in implementing North Sumatra Busedah through the fun school movement. The results showed that researchers designed the creation of North Sumatra Busedah as a history book renewal, which was adjusted to the learning outcomes in phases E and F. Two possible challenges will be faced in implementing North Sumatra Busedah to strengthen the character education of students through the fun school movement.